About C/539W1 and C/1245D1 as the parent comet of 15-BOOTIDS. (15th September 2021) - Martínez, M.J.; Marco, F.J.
Abstract: In a recent paper published in this journal it was presented an interesting study on the 2019 outburst of the 15-Bootids and it was suggested the possibility that comet C/539W1 was the parent comet of this meteor shower. It was also deducted from the method employed that this parent comet could have had a first passage through perihelion around the year AD1260. In this paper, we review both assumptions and we propose the possibility that the previous perihelion passage of the parent comet of the 15-Bootids was observed and recorded as C/1245D1. Highlights: We consider the paper of Jenniskens et al. published in this journal (10.1016/j.pss.2019.104829). We review the possibility that comet C/539W1 was the parent comet of the 15-Bootids meteor shower. The previous perihelion passage of the parent comet of the 15-Bootids may have been observed and recorded as C/1245D1.